Efektivitas Penerapan Metode Problem Solving pada Proses Pembelajaran Dasar Listrik dan Elektronika - Aryo Nugroho; Dwiprima Elvanny Myori (Jurnal Pendidikan Teknik Elektro, 2020)
The learning process in SMKN 3 Bungo is still centered on educators, in the learning process teachers dominate learning more than students and the learning method factors used are less appropriate, this can be seen from the lack of active role of students in the learning process and prefer to listen to the teacher's explanation, lack of interest and motivation of students in following the learning, as well as the lack of enthusiasm of students to solve problems in the learning process, where such a learning process affects the learning scores of students who have not achieved the Minimum Completeness Criteria (KKM). Therefore, Problem Solving learning methods are used to solve these problems in order to help students in more active and creative learning. The purpose of the study is to know the effectiveness of the use of Problem Solving methods against students' learning outcomes. This type of research uses pre-experimental research with the design of one group pretest-posttest as well as the subject of grade X TAV 2 SMKN 3 Bungo. The instrument used is a question of objective questions. The data obtained was analyzed using an analysis of student learning completeness and effect size. Based on the results of research the Problem Solving method has effectiveness towards students' learning outcomes in Basic Electrical and Electronic subjects at SMKN 3 Bungo